Towards a stronger food sector - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Small scale food processing in Mozambique, South Africa and Zambia: Addressing information and communication management needs for sector development Study Report. K Atkinson et al. CTA, 2000. 60 pp. ISBN 92 9081 2273 CTA number 985, 10 credit points